WsBot: A Tiny, Low-Cost Swarm Robot for Experimentation on Industry 4.0 - Limeira, Marcelo; Piardi, Luis; Kalempa, Vivian; Oliveira, André; Leitão, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Multi-Robot Systems (MRS) are a powerful tool to achieve machine-to-machine connectivity and intelligent behaviors required to Industry 4.0. However, these systems require that a large number of resources such as software, hardware, and mechanical devices working together. For reasons of cost, complexity and time they are usually validated only in simulated environments, thus causing great difficulty in their practical experimentation. This paper presents the WsBot, a tiny swarm robot of low cost, designed mainly, but not restricted, for the testing in smart factories. This robot is specially designed to present similar features of industrial agents, e.g., forklifts aiming to achieve the autonomous intelligent behaviors, individually, in groups or terms of the global task. The WsBot is a tiny differential robot, ROS-based, capable of executing its behavior and connects with other agents through Wi-Fi. These characteristics allow this robot to serve as a bridge so that researches, that until then were restricted to the theoretical and academic environment can effectively bring real contributions to smart factories.